Silver fused conducting fiber formation of Au-Ag core-shell nanoparticles mediated by ascorbic acid - Murugadoss, A.; Kar, Manoranjan; Pasricha, Renu; Chattopadhyay, Arun (Plasmonics, 2009)
In this paper, we report the spontaneous formation of fibrous structures consisting of assemblies of Au-Ag core-shell nanoparticles (NPs) from a solution consisting of Au-Ag core-shell NPs and l-ascorbic acid (AA). AA acted both as the reducing agent for the generation of NPs and also as the mediator for the formation of fibers. The process of fiber formation involved three steps-reduction of HAuCl(4) to Au NPs by AA, subsequent formation of Au-Ag core-shell NPs after addition of AgNO(3), and spontaneous formation of fibers from the mixtures in water. It took typically about 30 days to form complete fibers that are of lengths of several hundred micrometers to millimeters, although nanofibers started forming from the first day of solution preparation. The width of each of these fibers was typically about 1-4 A mu m with length of each segment of fiber bundle, on the order of 40 A mu m. Formation of fibers was also observed in absence of AgNO(3). These fibers consisted of Au NPs and polymer of AA degradation products and were not electrically conducting. Also, low concentrations of AgNO(3) produced fibers with low electrical conductivity. However, it was observed that increase in the amount of AgNO(3) leads to the formation of fibers that were electrically conducting with conductivity values in the range of metallic conductivity. Spectroscopic and electron microscopic investigations were carried out to establish the formation of fibers. The details of fiber formation mechanism under different conditions and electrical conductivities of the fibers are discussed in the article.
Keywords: Ascorbic acid; core-shell; Fiber; Gold; Nanoparticles; Silver